Strategi Pemasaran UMKM Jamu Mitra Rahayu di Pedukuhan Kalangan, Kelurahan Kebonagung - Luthfi Wahyu H; Anindya Putri M; Selviana W Selviana W; M. Reis Flandy; M. Naufal A; Zulya Amayra R Amayra R; Erda Wyne Astuti U; Modou Lamin J; Danang Wahyu M (Universitas Muhammadiyah Yogyakarta, 2023)
Pengabdian masyarakat ini berfokus pada kemitraan dengan UMKM jamu